2011
DOI: 10.1002/jcb.23356
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cancer stem cells in vincristine preconditioned SGC7901 gastric cancer cell line

Abstract: Cancer stem cells (CSCs), or tumor initiating cells, are a subpopulation of cancer cells with self-renewal and differentiation properties. However, there has been no direct observation of the properties of gastric CSCs in vitro. Here we describe a vincristine (VCR)-preconditioning approach to obtain cancer stem-like cells (CSLCs) from the gastric cancer cell line SGC7901. The CSLCs displayed mesenchymal characteristics, including the up-regulated mesenchymal markers Snail, Twist, and vimentin, and the down-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 54 publications
5
65
0
Order By: Relevance
“…It was previously reported that synchronous ovarian metastasis was an unfavorable factor correlated with poor survival (14), which was consistent with our study, suggesting that the metastasis-free interval was shortened between primary tumor diagnosis and ovarian metastasis.…”
Section: Univariate Analysis Multivariate Analysis ------------------supporting
confidence: 93%
“…It was previously reported that synchronous ovarian metastasis was an unfavorable factor correlated with poor survival (14), which was consistent with our study, suggesting that the metastasis-free interval was shortened between primary tumor diagnosis and ovarian metastasis.…”
Section: Univariate Analysis Multivariate Analysis ------------------supporting
confidence: 93%
“…Briefly, Transwell units with 8.0-µm-pore polycarbonate filters (Corning Incorporated, Corning, NY, USA) were precoated with 50 µl of 1:5 diluted Matrigel (BD Biosciences, Franklin Lakes, NJ, USA). A total volume of 200 µl of gastric cancer cell suspension, which contained ~1x10 5 rapamycin-treated cells, was added to the upper compartment of the precoated units. The units were then transferred to the wells of the culture plate and incubated for 24 h at 37˚C.…”
Section: Methodsmentioning
confidence: 99%
“…In numerous types of cancer, including gastric cancer, CD44 has been associated with increased invasion, metastasis and poor prognosis (3,4). This molecule has also been identified as a marker of stem-like gastric cancer cells (5,6); however, its role in this phenotype remains to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…The PKH-26 hi cells are highly enriched in CSCs (*1:1), and represent the only cell subset capable of reconstituting a mammary tumor; thus, suggesting that breast CSCs undergo a limited number of divisions. Other researchers have also used this strategy to isolate CSCs from different types of human tumors, such as gastrointestinal cancers, glioblastomas, and nasopharyngeal carcinomas [160][161][162][163].…”
Section: Cancer Cell Divisionmentioning
confidence: 99%